Gathered leaves - Soth, Alec 1969-; Chaplin, Lewis 1992- (MACK, 2015)
"This catalogue is a special object, bringing together an essay by Aaron Schuman spread across 28 large format postcards, with mini facsimile versions of Soth’s 4 books [3 of which are now out-of-print], all housed together in a luxurious printed and embossed clamshell box. One additional card printed with an introduction by Kate Bush, curator of the exhibition and Director of Media Space, London" - mackbooks.co.uk
Die Vorlage enthält insgesamt 5 Werke: "Sleeping by the Mississippi", "Niagara", "Broken Manual" und "Songbook". - Textblatt mit Anmerkungen von Kate Bush. - Enthält 28Colorprints mit erläuterndem Text auf der Rückseite jedes Prints; Textbeiträge meistens von Aaron Schuman
Published to accompany the exhibition Gathered leaves: the photographs of Alec Soth. Media Space, London, 6 October 2015-28 March 2016; National Media Museum, Bradford, May-July 2016; Finnish Museum of Photography, Helsinki, Aug.-Nov. 2016; FoMu, Antwerp, February-June 2017
Keywords: Soth, Alec -- 1969-; Fotografie; Kunst; Soth, Alec 1969- / Exhibitions; Artists' books; Photography, Artistic; Ausstellungskatalog